Suicide Risk Screening and Suicide Prevention in Patients With Cancer. Issue 4 (4th June 2021) - Gascon, Bryan; Leung, Yvonne; Espin-Garcia, Osvaldo; Rodin, Gary; Chu, Dominic; Li, Madeline
Abstract: Background: Suicide rates are up to 4 times greater in cancer compared with the general population, yet best practices for institutional suicide prevention are unknown. The objective of this study was to examine the association between suicide risk screening (SRS), clinician response, and suicide mortality at a comprehensive cancer treatment center. Methods: We conducted a naturalistic, retrospective cohort study of patients attending the Princess Margaret Cancer Centre, where routine screening for suicidal intent within the Distress Assessment and Response Tool (DART-SRS) was implemented in 2010. Inverse probability of treatment weighting was used to evaluate the impact of DART-SRS completion on suicide mortality from 2005 to 2014. Chart audits were conducted for clinician response to suicidality, and crude suicide rates over the study period were analyzed. All statistical tests were 2-sided. Results: Among 78 650 cancer patients, 89 (0.1%) died by suicide, of whom only 4 (4.5%) had completed DART-SRS. Among DART-SRS completers (n = 14 517), 69 (0.5%) reported suicidal intent, none of whom died by suicide. DART-SRS completion was associated with increased clinician response to suicidality (17.4% vs 6.7%, P  = .04), more psychosocial service usage (30.5% vs 18.3%, P  < .001), and lower suicide mortality (hazard ratio = 0.29, 95% confidence interval = 0.28 to 0.31). Crude suicide rates at the Princess Margaret Cancer Centre were lower in patients whose first contact year was after DART-SRS implementation. Conclusion: DART-SRS completion is associated with lower suicide mortality and increased access to psychosocial care, but patients who did not complete DART-SRS were at highest suicide risk. Further research is needed to identify mechanisms to ensure psychosocial and suicidality assessment in cancer patients who do not complete SRS.